The Nurses' Attitudes Towards Research as influenced by their Research Competence in Private Healthcare Facilities in North Cotabato, Philippines - Maglunsod, Helen Prieto; Kulintang, Mohammed Bien M. (Future Science / FSH-PH Publications, 2024)
It is empirical that nurses must receive education and training to strengthen their research skills to apply evidence-based practice. This study aimed to ascertain how nurses' views toward undertaking research in private healthcare facilities correlated with their capacity for research. A predictive-correlational design was used in the study. 120 nurses were conveniently selected and included in the research. An adapted survey questionnaire from the study of Bostrom et al. (1989) and Perez et al. (2022) was used for data gathering. Results showed that majority of the respondents were female in their middle-age who had worked in the healthcare facility’s ward for two years or less. Their attitude toward research undertaking and ability were both quite excellent. Nurses' attitudes regarding performing research and their research competence were significantly correlated. However, there was no discernible correlation between attitudes and the demographic profile. Furthermore, the nurses’ research abilities greatly influence their attitudes toward performing research. These results show that nurses can undertake research and have a positive attitude toward it. The study emphasizes the need to strengthen these skills through education and training by highlighting the strong association between nurses' research capacities and their positive attitude toward undertaking research. Developing nurses' research abilities fosters an environment where practice is increasingly grounded on evidence.